2010
DOI: 10.1021/jf102551f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Enological Potential of Raboso Varieties by Study of Secondary Grape Metabolites

Abstract: DNA studies supported by matrix-assisted laser desorption ionization-time of flight mass spectrometry analysis of seed proteins showed that the Vitis vinifera red grape variety Raboso Veronese is the progeny of a spontaneous cross between Raboso Piave (red) and Marzemina Bianca (white) varieties. In the present work, the main secondary grape metabolites of Raboso varieties were studied, and their enological potential was evaluated and compared with that of other red varieties reported in the literature. In gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…On the contrary, the increase of acylated anthocyanins observed in Corvina is in agreement with previous findings reported for this variety . On the other hand, withering conditions used for the two varieties were the same and these differences are reasonably a variety‐dependent effect, and the decrease of acyl anthocyanins observed in Raboso Piave can be because of particular high content of anthocyanins of this variety …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the contrary, the increase of acylated anthocyanins observed in Corvina is in agreement with previous findings reported for this variety . On the other hand, withering conditions used for the two varieties were the same and these differences are reasonably a variety‐dependent effect, and the decrease of acyl anthocyanins observed in Raboso Piave can be because of particular high content of anthocyanins of this variety …”
Section: Resultssupporting
confidence: 91%
“…[16] On the other hand, withering conditions used for the two varieties were the same and these differences are reasonably a variety-dependent effect, and the decrease of acyl anthocyanins observed in Raboso Piave can be because of particular high content of anthocyanins of this variety. [58] Figure 2a and 2b Supporting Information show the correlation among the metabolites in Raboso and Corvina, respectively.…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…Fining of Raboso red wine, a wine typically rich in phenolic substances (De Rosso et al ), showed that, regardless of the dosage used, GSE resulted in a significant reduction of the concentration of phenolic substances, removing an average of 65 mg/L of phenolic substances from the Control wine, a value similar to that removed by addition of egg albumin (−94 mg/L), gelatin (−66 mg/L) and patatin (−46 mg/L) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Raboso Piave is another red grape variety cultivated in the Veneto region, whose grapes are characterized by high polyphenolic content, used to produce the high-quality reinforced wine Raboso Passito DOCG [1].…”
Section: Introductionmentioning
confidence: 99%